Postcolonial-interreligious dialogue: A case study of the Silsilah Dialogue Movement - Corpuz, Jeff Clyde Guillermo (Animo Repository, 2023)
This dissertation examines how the Silsilah Dialogue Movement (SDM) can be analyzed and further enhanced by a postcolonial-interreligious perspective. Using various perspectives from postcolonial theologians, this dissertation appropriates an Asian postcolonial approach to interreligious dialogue (IRD), as well as, Andrew Orton’s Interfaith Dialogue: Seven Key Questions for Theory, Policy and Practice. These were used as lens to analyze the SDM in Zamboanga, Mindanao. The study employs qualitative methods such as participant observation, interviews, and focus group discussion to collect data and engage in theological discourse. Interviews were transcribed, read, and processed using thematic analysis. The data gathered and interpreted in this research came from the insights from the members and leaders of SDM. The study shows that SDM possesses the following features of an Asian-postcolonial approach to IRD. 1) It is inclusive-pluralist, that is, it believes that multiple religions can coexist. In the SDM, one finds the active participation of women and the youth, grassroot sectors that are not often seen in traditional IRD. It also includes non-Islamic indigenous groups in the dialogue. indigenous peoples. 2) It is liberationist; it is not only confined to “religious concerns” but addresses socio-economic roots of conflict between Muslims and Christians/indigenous groups 3) It is contextualized or inculturated. It is inspired by Sufism which is the Islamic tradition that first found its way to the Philippines and blends well with folk practices. It also gives central importance to the Asian concept of harmony. 4) The goal of IRD for SDM is harmony which does not aim at abolishing difference (intra and interreligious differences) but rather at enriching one’s own religious heritage in the encounter with others. A significant feature of SDM as an Asian postcolonial IRD is its holistic approach; it fosters a Culture of Dialogue (COD) –dialogue with God, Self, Others, and Creation –as a path to peace. However, from a postcolonial perspective, SDM still has to recognize the importance of gender as an issue that is integral to IRD from an intra-religious and inter-religious perspective. It has not engaged as well in intrareligious dialogue.